A facile synthesis of energetic salts based on fully nitroamino-functionalized [1, 2, 4]triazolo[4, 3-b][1, 2, 4]triazole. Issue 2 (11th December 2019) - Bian, Chengming; Feng, Wenjing; Lei, Qunying; Huang, Haifeng; Li, Xia; Wang, Jianlong; Li, Chuan; Xiao, Zhongliang
Abstract : Promising high-energy-density materials: energetic salts based on fully nitroamino-functionalized [1, 2, 4]triazolo[4, 3- b ][1, 2, 4]triazole. Abstract : A novel family of fully nitroamino-functionalized [1, 2, 4]triazolo[4, 3- b ][1, 2, 4]triazole-based energetic salts were synthesized. All salts were characterized by IR and multinuclear NMR spectroscopy, thermal analysis and elemental analysis. The crystal structures of salts 5, 6, and 7 were confirmed by single-crystal X-ray diffraction. The densities of these salts are between 1.65 (4 ) and 1.89 g cm −3 (3 ), whilst their oxygen balances are between −42.8% (7 ) and −11.3% (3 ). Theoretical performance calculations (Gaussian 09 and EXPLO 6.01) provided detonation pressures and velocities for salts 2–7 in the ranges of 27.6–41.1 GPa and 8519–9518 m s −1, respectively, which make them competitive energetic materials.